2015
DOI: 10.3324/haematol.2015.126938
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression and in vitro function of mesenchymal stromal cells are affected in juvenile myelomonocytic leukemia

Abstract: An aberrant interaction between hematopoietic stem cells and mesenchymal stromal cells has been linked to disease and shown to contribute to the pathophysiology of hematologic malignancies in murine models. Juvenile myelomonocytic leukemia is an aggressive malignant disease affecting young infants. Here we investigated the impact of juvenile myelomonocytic leukemia on mesenchymal stromal cells. Mesenchymal stromal cells were expanded from bone marrow samples of patients at diagnosis (n=9) and after hematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Wnt/β-catenin signaling in the NP on the other hand progressively increased from E18.5 to 5 weeks of age 36 . Thus, the compartment-specific expression of canonical Wnt inhibitors such as SFRP1, SFRP4, DKK1, and APCDD1L [37][38][39][40] may be one of the mechanisms employed to modulate Wnt/β-catenin signaling in the AF. On the other hand, higher expression of WNT5A may suggest important roles of non-canonical Wnt signaling 41 in AF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signaling in the NP on the other hand progressively increased from E18.5 to 5 weeks of age 36 . Thus, the compartment-specific expression of canonical Wnt inhibitors such as SFRP1, SFRP4, DKK1, and APCDD1L [37][38][39][40] may be one of the mechanisms employed to modulate Wnt/β-catenin signaling in the AF. On the other hand, higher expression of WNT5A may suggest important roles of non-canonical Wnt signaling 41 in AF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modifications of the inflammatory status induced by therapy can reshape the immunomodulatory activity of MSCs. In patients with juvenile myelomonocytic leukemia, MSCs showed differential mRNA expression, including genes involved in immunomodulation, that normalized when disease remission was achieved after HSCT [ 59 ]. If MSCs can affect immune-based therapies remains to be elucidated.…”
Section: How Aml and Its Niche Affect Immunotherapymentioning
confidence: 99%
“…Tian et al, studied T helper subsets in AML patients and found that, while Th1, Th2, Th17, and Th22 cells and IL-22 were significantly reduced, Treg cells were increased in newly diagnosed AML patients compared to patients in remission or controls and chemotherapy ameliorated these variations [ 97 ]. MSC-mediated alteration of immune environment may be reversible with leukemia treatment, as also shown in patients with juvenile myelomonocytic leukemia, whose MSCs showed differential mRNA expression, including genes involved in immunomodulation and cell–cell interaction, that normalized during remission after successful hematopoietic stem cell transplantation [ 98 ].…”
Section: Mscs and Tumor Immune Escapementioning
confidence: 99%